Comprehensive characterization and kinetic analysis of coconut shell thermal degradation: Energy potential evaluated via the Coats-Redfern method - Monir, Minhaj Uddin; Muntasir Shovon, Shaik; Akash, Faysal Ahamed; Habib, Md Ahosan; Techato, Kuaanan; Azrina, Abd Aziz; Chowdhury, Shahariar; Eka Prasetya, Tofan Agung (Elsevier Ltd, 2024)
Coconut shell represents a promising biomass for energy production, given their wide availability. In this study, the thermo-kinetics of coconut shells were examined through thermogravimetric analysis from 30 °C to 1000 °C at 5 °C/min under N2. Advanced analytical tools assessed the elemental, microstructural, and morphological attributes of the samples. The thermal degradation unveiled three phases: dehydration, devolatilization, and combustion. Notably, the Coats-Redfern method detailed the devolatilization stage, pinpointing the coconut shell's thermal and kinetic attributes. The Zhuravlev diffusion equation (DM6) emerged as the most suitable model, with an activation energy (Ea) and pre-exponential factor of 68.9 kJ mol−1 and 0.05 min−1, respectively. Thermodynamic values such as enthalpy (ΔH), Gibbs free energy (ΔG), and entropy (ΔS) for devolatilization were 65.2, 193.1, and −0.28117, respectively. Collectively, the findings underscore the significant bioenergy potential of coconut shells, positioning them as a sustainable alternative to traditional energy. Such insights play a crucial role in improving pyrolysis reactor designs and comprehending the mechanisms of coconut shell pyrolysis, offering potential solutions for energy deficits and environmental concerns.